Crafting civilian control of the military in Venezuela : a comparative perspective - Trinkunas, Harold A. (University of North Carolina Press, 2005)
The transition from military rule to democracy in Venezuela has been sustained over four decades, during which time civilian control over the armed forces has become markedly institutionalised. This book explores the political forces at work in the country.